Pengaruh Lingkungan Keluarga, Prestasi Belajar, dan Kesejahteraan Guru Terhadap Minat Menjadi Guru Akuntansi - Elsa Dwi Indrianti; Agung Listiadi (Jurnal Pendidikan Akuntansi (JPAK), 2021)
Interest in becoming an educator arises because of a willingness from oneself and is strengthened by several other factors. This research was conducted to analyze the variables of the family environment, learning achievement and teacher welfare on the interest in becoming an accounting teacher. The type of research used in this study is quantitative with a population of 320 students in the Accounting Education Study Program, Faculty of Economics and Business, State University Of Surabaya. Data obtained from documents and distributing questionnaries to 178 respondents. This study used proportional random sampling technique. The data analysis technique used Multiple Linear Regression by IBM SPSS 20 for windows application. The results of the analysis show that the family environment, learning achievement and teacher welfare simultaneously have a significant influence on the interest in becoming an accounting teacher. Family environment has a direct influence on interest in becoming an accounting teacher. Learning achievement has a direct influence on interest in becoming an accounting teacher. And teacher welfare also has a direct influence on interest in becoming an accounting teacher.